Growth processes of high-growth firms as a four-dimensional chicken and egg. (3rd October 2016) - Coad, Alex; Cowling, Marc; Siepel, Josh
Abstract: This article investigates whether high-growth firms grow in different ways from other firms. Specifically, we analyze how firms grow along several dimensions (growth of sales, employment, assets, and operating profits) using Structural Vector Autoregressions. Causal relations are identified by using information contained in the (non-Gaussian) growth rate distributions. For most firms, the growth process starts with employment growth, which is then followed by sales growth, then growth of operating profits, and finally growth of assets. In contrast, high growth firms put more emphasis on growth of operating profits driving other dimensions of growth, with employment growth occurring at the end.